Extracts of Clove (Syzygium aromaticum) Potentiate FMSP-Nanoparticles Induced Cell Death in MCF-7 Cells - Khan, Firdos Alam; Akhtar, Sultan; Almohazey, Dana; Alomari, Munthar; Almofty, Sarah Ameen (International Journal of Biomaterials, 2018)
Both nanoparticles and cloves (Syzygium aromaticum) possess anticancer properties, but they do not elicit a significant response on cancer cells when treated alone. In the present study, we have tested fluorescent magnetic submicronic polymer nanoparticles (FMSP-nanoparticles) in combination with crude clove extracts on human breast cancer cells (MCF-7) to examine whether the combination approach enhance the cancer cell death. The MCF-7 cells were treated with different concentrations (1.25 μg/mL, 12.5 μg/mL, 50 μg/mL, 75 μg/mL, and 100 μg/mL) of FMSP-nanoparticles alone and in combination with 50 μg/mL crude clove extracts. The effects of FMSP-nanoparticles alone and combined with clove extracts were observed after 24 hrs and 48 hrs intervals. The response of FMSP-nanoparticles-treated cells was evaluated by Trypan Blue, 4′,6-diamidino-2-phenylindole (DAPI), and 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assays, respectively. We have demonstrated that cancer cell viability was decreased to 55.40% when treated with FMSP-nanoparticles alone, whereas when cancer cells were treated with FMSP-nanoparticles along with crude clove extracts, the cell viability was drastically decreased to 8.50%. Both morphological and quantitative data suggest that the combination of FMSP-nanoparticles plus crude clove extracts are more effective in treating cancer cells and we suggest that the combination treatment of nanoparticles along with clove extracts hold a great promise for the cancer treatments.